2019
DOI: 10.1080/10428194.2019.1678153
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of chromatin remodeling and tyrosine kinase genes in iAMP21-positive acute lymphoblastic leukemia

Abstract: Intrachromosomal amplification of chromosome 21 (iAMP21) is a cytogenetic subtype associated with relapse and poor prognosis in pediatric B-cell precursor acute lymphoblastic leukemia (BCP ALL). The biology behind the high relapse risk is unknown and the aim of this study was to further characterize the genomic and transcriptional landscape of iAMP21. Using DNA arrays and sequencing, we could identify rearrangements and aberrations characteristic for iAMP21. RNA sequencing revealed that only half of the genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…However, the resolution of the algorithm might be too low to reliably detect iAMP21. We thus, analyzed the expression of DYRK1A and CHAF1B that have recently been associated with iAMP21-positive ALLs [ 33 ]. The expression of both genes was indeed heightened in the iAMP21 case (Additional file 2 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the resolution of the algorithm might be too low to reliably detect iAMP21. We thus, analyzed the expression of DYRK1A and CHAF1B that have recently been associated with iAMP21-positive ALLs [ 33 ]. The expression of both genes was indeed heightened in the iAMP21 case (Additional file 2 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study from Öfverholm et al (17) identified MORC3, SON, CHAF1B and DYRK1A as potential candidates for the iAMP21 pathophysiology. In our study, MORC3, CHAF1B, and DYRK1A, located in the CRA, were upregulated, but less strongly than RIPPLY3 (CHAF1B: R = 0.32) or not at all correlated to the iAMP21 signature (MORC3: R = -0.034; DYRK1A: R = 0.004).…”
Section: Discussionmentioning
confidence: 99%
“…However, Rand et al (4) show that the amplification is not completely random, with a region that is amplified in 18 studied cases of 5.1 Mb spanning from 32.8 to 37.9 Mb (hg18). This amplified region contains 86 genes (coding and non-coding) (4), and even though some of these genes are highly overexpressed in iAMP21 (17), none of these genes have yet been identified to be causally deregulated by the amplification. Besides overexpression of genes on chromosome 21 (cis-effect), many genes outside of chromosome 21 are overexpressed as well (17), opening up the possibility of an indirect leukemic effect of chromosome 21 amplification (trans-effect).…”
Section: Introductionmentioning
confidence: 99%
“…Human DYRK1a gene locus amplification is associated with Down syndrome and B-ALL, and a role for DYRK1a in regulating B-ALL has also been suggested in a mouse model study. 20,40,41 Our analysis of a human pediatric ALL database revealed DYRK1a amplification or mRNA overexpression in 10.83% of total cases. Integration of DYRK1a inhibitor into the treatment of DYRK1a hi ALL population may improve the outcomes.…”
Section: Discussionmentioning
confidence: 88%